Inequalities in mortality among refugees and immigrants compared to native Danes - a historical prospective cohort study - Norredam Marie; Olsbjerg Maja; Petersen Jorgen H; Juel Knud; Krasnik Allan (BMC, 2012)
Abstract Background Comparisons of mortality patterns between different migrant groups, and between migrants and natives, are relevant to understanding, and ultimately reducing, inequalities in health. To date, European studies on migrants' mortality patterns are scarce and are based solely on country of birth, rather than migrant status. However, mortality patterns may be affected by implications in relation to migrant status, such as health hazards related to life circumstances before and during migration, and factors related to ethnic origin. Consequently, we investigated differences in both all-cause and cause-specific mortality from cancer and cardiovascular disease among refugees and immigrants, compared with the mortality among native Danes. Methods A register-based, historical prospective cohort design. All refugees (n = 29,139) and family-reunited immigrants (n = 27,134) who, between 1 January1993 and 31 December1999, were granted right of residence in Denmark were included and matched 1:4 on age and sex with native Danes. To identify deaths, civil registration numbers were cross-linked to the Register of Causes of Death (01.01.1994-31.12.2007) and the Danish Civil Registration System (01.01.1994-31.12.2008). Mortality rate ratios were estimated separately for men and women by migrant status and region of birth, adjusting for age and income and using a Cox regression model, after a median follow-up of 10-13 years after arrival. Results Compared with native Danes, all-cause mortality was significantly lower among female (RR = 0.78; 95%CI: 0.71;0.85) and male (RR = 0.64; 95%CI: 0.59-0.69;) refugees. The rates were also significantly lower for immigrants: women (RR = 0.44; 95%CI: 0.38;0.51) and men (RR = 0.43; 95%CI: 0.37;0.51). Both migrant groups also had lower cause-specific mortality from cancer and cardiovascular diseases. For both all-cause and cause-specific mortality, immigrants generally had lower mortality than refugees, and differences were observed according to ethnic origin. Conclusions Mortality patterns were overall advantageous for refugees and immigrants compared with native Danes. Research should concentrate on disentangling the reasons behind migrants' health advantages, in order to enlighten future preventive public-health efforts, for the benefit of the entire population.